2010
DOI: 10.1111/j.1528-1167.2010.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with nonbenzodiazepine antiepileptic drug intoxication: Analysis of 9,809 registered cases of drug poisoning

Abstract: SUMMARYPurpose: Antiepileptic drug (AED) intoxications are common due in part to wide clinical application and availability. Because AEDs usually depress central nervous system function, overdosing may be potentially life-threatening or lead to a range of adverse outcomes. The aim of this study was to identify risk factors for nonbenzodiazepine AED (NBAED) intoxication. Methods: In this cross-sectional study, all consecutive adult and adolescent (>12 years old) poisoned patients who presented to the Loghman-Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
(25 reference statements)
4
12
0
Order By: Relevance
“…In our study, the most commonly encountered drug was carbamazepine which generally corresponded with community prescribing patterns. It is also compatible with reports from Edinburgh [6], Iran (Tehran) [9], and São Paulo [5]. Another frequently used drug in our study was valproic acid.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the most commonly encountered drug was carbamazepine which generally corresponded with community prescribing patterns. It is also compatible with reports from Edinburgh [6], Iran (Tehran) [9], and São Paulo [5]. Another frequently used drug in our study was valproic acid.…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of deliberate self-poisoning was 94.86% in our study. Suicide attempt was the most frequent circumstance observed in Brazil (Saõ Paulo) [5] and Iran (Tehran, 98.9%) [9], too.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Poisonings with drugs are more frequent in the young adult groups in our country as it is all over the world (3,9,(11)(12)(13). In a study from Iran, which included all age groups, it is reported that 43.2% of the patients who were poisoned with NBDAED were between the ages of 20-30 (8).…”
Section: Discussionmentioning
confidence: 94%
“…Another reason could be that, in some patients, loneliness is the cause or comorbidity of a psychological or somatic disease or that it even acts as a side effect of medication use (Hassanian-Moghaddam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%